Pengelolaan Perikanan Skala Kecil di Perairan Pesisir Kota Semarang - Jamaludin Malik; Dietriech Geoffrey Bengen; Taryono Taryono (Institut Pertanian Bogor, 2021)
Overfishing can occur in open access fisheries, where fishermen conduct fishing activities without restrictions. Fisheries management based on biological factors alone (Maximum Sustainable Yield approach) is considered inadequate because it does not consider socio-economic aspects in fisheries management. The study aims to analyze the utilization of small-scale fishery resources in Semarang City and determine its policies to be sustainable. Bioeconomic analysis was used to optimize the utilization of fishery resources. Small-scale fisheries management strategic policies, used analysis of Interpretative Structural Modeling (ISM). The results showed utilization of small scale fishery resources in Semarang City can be achieved with optimal production of anchovy (Stolephorus spp.) 1,477.79 tons/year and optimal effort of 324 units; optimal production of Tembang (Sardinella fimbriata) 235.96 tons/year and optimal effort of 516 units; optimal production of mackerel (Rastrelliger kanagurta) 28.51 tons/year and optimal effort of 479 units; and optimal production of Petek (Leiognathus sp.) 25.54 tons/year and optimal effort of 847 units. In conclusion, the Anchovy (Stolephorus spp.) resources have experienced overfishing since 2007-2008; Mackerel (Rastrelliger kanagurta) resources overfishing occurred from 2009-2015; and Petek (Leiognathus sp.) resources have experienced overfishing since 2014-2016; while Tembang (Sardinella fimbriata) resources have not experienced overfishing because they are not the main target. The key sub-elements of small-scale fisheries management in Semarang City include: a) fishermen; b) Semarang City Fisheries Agency; c) overcapacity; d) decreasing catches; e) environmentally unfriendly arrests; f) ineffective regulation; g) conservation fish resources; h) increasing fishermen's income; i) limitation environmentally unfriendly fishing gear. Keywords: bioeconomic, fisheries, management, MEY, Maximum Sustainable Yield